Ortodoncia y cirugía ortognática: ventajas y limitaciones de la planificación 3D con respecto a la planificación 2D y cirugía de modelos de escayola. - FERRANDO CASCALES, RAÚL; DE PAZ SÁNCHEZ, RAFAEL; VINCENT FRAILE, GERMÁN; BRAVO GONZÁLEZ, LUIS ALBERTO (Revista Española de Ortodoncia, 2015)
Classical 2D planning and surgery plaster models have had and still have a key role in the protocol regarding orthodontic-surgical treatments. However, new technologies such as cone beam computed tomography, intraoral scanners, and computer programs will broaden the horizon of vision of clinical cases, providing precision and accuracy to our planning. The purpose of this paper is to determine which cases we consider advisable to be planned using 3D and which other cases could be planned by 2D and traditional plaster model surgery. We will review the current literature on the subject and illustrate our findings with a planned clinical case with two procedures: 3D planning and 2D planning with traditional plaster surgery. In addition, we review the limitations of 3D planning as it is a technique in constant progress with areas where it is not yet predictable. Conclusion: The use of 3D planning is indicated in some cases, but there are still limitations that should not be underestimated.